The man who died twice - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club, 2021)
"Richard Osman is back with everyone's favorite mystery-solving quartet, and the second installment of The Thursday Murder Club series is just as clever and warm as the first-an unputdownable, laugh-out-loud pleasure of a read"--